Agama dan Budaya: Analisis Bibliometrik pada Database Dimensions - Fitri Nur Syahidah (Gunung Djati Conference Series, 2023)
This study aims to discuss research data and publications related to Religion and Culture. The author's research method uses data from international publications with quantitative research methods in the theme of Religion and Culture by collecting data using bibliometric analysis. The results with the discussion of this study are explained regarding the results of research or observations that have been researched by previous authors. The following of all the number of linkages is presented in graphical form. From the analysis that was carried out, it resulted that a lot of research or observations made regarding Religion and Culture have been carried out every year, especially counting from the year the author listed.